THE OBJECTIVE OF THIS STUDY IS TO EXAMINE THE EFFICACY OF THE ULTRASONIC WELDING PROCESS FOR JOINING TEXTILE POLYMER MATERIALS. - Butovskiy P.M.; Palvannazirova N.A. (TADQIQOTLAR.UZ, 2024)
A new technological way to connect textile polymeric materials - ultrasonic welding, the results of research welds com- pound textile materials strength of the breaking load. Ultrasonic welding represents a novel technological approach to the joining of materials, situated between the domains of welding and pressure welding. The scope of applications for ultrasonic welding is more extensive than that of high-frequency and thermal contact welding. The method can be employed to join textiles comprising a range of thermoplastic fibers. The principal advantages of ultrasonic technologies are their simplicity of application, absence of consumables, and ease of automation, which allows for the integration of ultrasonic welding modules into technological lines. The most significant benefit is the environmentally friendly nature of the processes, which renders these technologies an attractive proposition in the context of modern production.